Предмет: Математика,
автор: dgritsay2002
Помогите, пожалуйста!
Приложения:
Ответы
Автор ответа:
0
Выразим из первого уравнения х и подставим во 2 уравнение
х=-у-3
(-у-3)²+у²=5
у²+6у+9+у²-5=0
2у²+6у+4=0
у²+3у+2=0
у1+у2=-3 и у1*у2=2
у1=-2⇒х1=2-3=-1
у2=-1⇒х2=1-3=-2
Ответ (-1;-2);(-2;-1)
х=-у-3
(-у-3)²+у²=5
у²+6у+9+у²-5=0
2у²+6у+4=0
у²+3у+2=0
у1+у2=-3 и у1*у2=2
у1=-2⇒х1=2-3=-1
у2=-1⇒х2=1-3=-2
Ответ (-1;-2);(-2;-1)
Похожие вопросы
Предмет: Химия,
автор: nawmora235
Предмет: Українська мова,
автор: gajdukvera19159
Предмет: Английский язык,
автор: princess2021
Предмет: Литература,
автор: annakrytayu
Предмет: География,
автор: andron2005